Complete coding region sequence analyses and antigenic characterization of emerging lineage G-IX of foot- and-mouth disease virus serotype Asia1 - Manoranjan Rout; Shyam Singh Dahiya; Saravanan Subramaniam; Ramakant Acharya; Reshama Samanta; Jitendra Kumar Biswal; Jajati Keshari Mohapatra; Rabindra Prasad Singh (Veterinary Quarterly)
Foot-and-mouth disease Virus (FMDV) serotype Asia1 is prevalent in the Indian subcontinent, with only G-III and G-VIII reported in India until 2020. However, in 2019, a novel genetic group within serotype Asia1, designated as G-IX, emerged in Bangladesh, followed by its detection in India in 2020. This report presents analyses of the complete coding region sequences of the G-IX lineage isolates. The length of the open reading frame (ORF) of the two G-IX isolates was 6990 nucleotides without any deletion or insertion. The G-IX isolates showed the highest sequence similarity with an isolate of G-III at the ORF, L, P2, and P3 regions, and with an isolate of G-VIII at the P1 region. Phylogenetic analysis based on the capsid region (P1) supports the hypothesis that G-VIII and G-IX originated from a common ancestor, as speculated earlier. Further, VP1 region-based phylogenetic analyses revealed the re-emergence of G-VIII after a gap of 3 years. One isolate of G-VIII collected during 2023 revealed a codon insertion in the G-H loop of VP1. The vaccine matching studies support the suitability of the currently used Indian vaccine strain IND63/1972 to contain outbreaks due to viruses belonging to G-IX.